PENGARUH PROGRAM PEMBELAJARAN GURU DAN PENGGUNAAN METODE PEMBELAJARAN MATEMATIKA TERHADAP PRESTASI BELAJAR SISWA PADA SMP NEGERI 5 MEUREUBO KABUPATEN ACEH BARAT - Salbidah .; Murniati .; Yusrizal . (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2018)
Teacher learning programs and methods is one of effective and efficient learning management effort in improving student achievement. This study aimed to determine the learning preparation programs; the preparation of lesson plans, learning site lesson plan implementation, evaluation and the use of mathematical learning methods on student achievement at SMP 5 Meureubo. This research used descriptive method with quantitative approach. The data collection techniques were observation, interviews, documentation and test. Subjects in this study were all the teachers and students at SMP 5 Meureubo. The results of this study showed that the courses organized by the school-based curriculum beginning of each semester admitted to the school principal. But there were still teachers who were not yet ready to put together a program of learning, while the learning process had occurred up to two months. Learning program was designed by teachers directed by the principal, and through the discussion forum of subject teachers (MGMPs), teachers develop syllabi according to the needs and circumstances of the school environment. The results of the data analysis simultaneously learning program teacher and the use of appropriate learning methods can affect the improvement of student achievement results. From the test results; 1) The study showed that learning preparation program, 2) Implementation of lesson plan, and 3) Evaluation of lesson plan, and mathematical learning method affected significantly and positively student achievement at SMP 5 of Meurreuboh of Aceh barat.Keywords: Learning Program and Student Achievement